KEDUDUKAN HUKUM PERJANJIAN TERAPEUTIK (ANTARA RUMAH SAKIT DAN PASIEN) DALAM PERSETUJUAN TINDAKAN MEDIK MENURUT KITAB UNDANG-UNDANG HUKUM PERDATA - Novika, Rozi Oktri; Hanifah, Mardalena; Hasanah, Ulfia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
At first the legal relationship between doctor and patient are vertical or paternalistic, but now changed along with the times and technological advances into horizontal contractual relationship, resulting in an agreement known as therapeutic agreement. The purpose from written this scripsion are; The First, the legal position of the therapeutic agreement (between the general hospital Dumai city and patients) in the approval of medical action under Article 1320 of the Civil Code, The Second, the rights and obligations of the parties in the therapeutic agreement (between the general hospital Dumai city and patients) in the approval medical action. This research method is a kind of normative legal research to the general principles of law.The conclusion are, The First, position regarding the legal agreement between the hospital and the patient does not create certainty, because under Article 1320 of the Civil Code or suitability konsesualisme opinion both parties must not only one party only. So if there is negligence or fault of health workers, patients would be difficult to prosecute.The Second, On approval of the installation of WSD (Water Seal Drainage) medical action in district general hospitals Dumai city, when seen in the agreement is not known who the doctor in charge, will cause the loss of the patient, because in case of errors or omissions committed the doctor, is not known to whom the patient will sueThis gives enormous influence to the patient in terms of asking for legal protection. Writter suggest, The First, the government should made law that specifically regulate this therapeutic agreement format, so that the uniformity of format in every hospital agreement. The Second, We recommend necessary to establish regulations governing the therapeutic agreement that it will also include the rights and obligations of the parties, so that there are special rules governing it and also establishes strict sanctions for health workers are guilty of negligence. So that health workers do their job very carefully and do not give rise to many more victims. Keywords: Therapeutic Agreement - hospital- Patients -Approval Medik